2015
DOI: 10.1590/1678-4162-8379
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem auditory evoked responses in healthy Argentine Mastiff dogs recorded with surface electrodes

Abstract: Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
2
8
1
Order By: Relevance
“…In the present study, the observed values of the wave latencies and intervals are lower than those described previously in other species like dogs (e.g., 1.098 ± 0.025 ms for latency I and 3.827 ± 0.226 ms for latency V [6] or 1.59 ± 0.1 ms for latency I and 5.56 ± 0.19 ms for latency V [19]) and ferrets where a value of 1.1 ± 0.09 ms for wave I latency and 3.8 ± 0.21 ms for wave V latency was reported [4]. Regarding the amplitudes, their values were similar or smaller than in other reports.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…In the present study, the observed values of the wave latencies and intervals are lower than those described previously in other species like dogs (e.g., 1.098 ± 0.025 ms for latency I and 3.827 ± 0.226 ms for latency V [6] or 1.59 ± 0.1 ms for latency I and 5.56 ± 0.19 ms for latency V [19]) and ferrets where a value of 1.1 ± 0.09 ms for wave I latency and 3.8 ± 0.21 ms for wave V latency was reported [4]. Regarding the amplitudes, their values were similar or smaller than in other reports.…”
Section: Discussioncontrasting
confidence: 91%
“…In our individuals, waves' morphology (wave I, II, III and V) ( Figure 1) was similar to the one described in dogs, cats, and other mammals [6][7][8]12,13]. In ferrets, Piazza et al (2014) observed that peak III consists of two peaks but that does not seem to be the case in our individuals.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations